Gender Differences in Negative Life Events, Present-Moment Awareness, Problem-Solving, and Perceived Stress Among Rural Adolescents. - Zhang, Yaoyao; Liu, Xin; Wu, Huimin; Guo, Cheng (Child Psychiatry & Human Development, 2026)
Drawing on the stressor–perception–coping–response model of stress, this study examined the associations between negative life events, present-moment awareness, problem-solving, and perceived stress among rural adolescents, focusing specifically on gender differences. Using a cross-sectional design, 3519 Chinese rural adolescents completed measures assessing negative life events, present-moment awareness, problem-solving, and perceived stress. Structural equation modeling was employed to examine the hypothesized serial mediation model. The results revealed a positive association between negative life events and perceived stress in rural adolescents, which was serially mediated by present-moment awareness and problem-solving. Furthermore, significant gender differences were observed. Specifically, girls exhibited larger effects than boys in the overall effect of negative life events on perceived stress, the indirect effect of present-moment awareness, and the serial mediating effect. These findings suggest that present-moment awareness and problem-solving may serve as crucial mechanisms for understanding rural adolescents' perceived stress in response to negative life events, particularly among female rural adolescents.